Uses of strength-based interventions for people with serious mental illness: a critical review - Tse, Samson; Tsoi, Emily W.S.; Hamilton, Bridget; O’Hagan, Mary; Shepherd, Geoff; Slade, Mike; Whitley, Rob; Petrakis, Melissa (SAGE Publications, 2016)
Background: For the past 3 decades, mental health practitioners have increasingly adopted aspects and tools of strength-based approaches. Providing strength-based intervention and amplifying strengths relies heavily on effective interpersonal processes. Aim: This article is a critical review of research regarding the use of strength-based approaches in mental health service settings. The aim is to discuss strength-based interventions within broader research on recovery, focussing on effectiveness and advances in practice where applicable. Method: A systematic search for peer-reviewed intervention studies published between 2001 and December 2014 yielded 55 articles of potential relevance to the review. Results: Seven studies met the inclusion criteria and were included in the analysis. The Quality Assessment Tool for Quantitative Studies was used to appraise the quality of the studies. Our review found emerging evidence that the utilisation of a strength-based approach improves outcomes including hospitalisation rates, employment/educational attainment, and intrapersonal outcomes such as self-efficacy and sense of hope. Conclusion: Recent studies confirm the feasibility of implementing a high-fidelity strength-based approach in clinical settings and its relevance for practitioners in health care. More high-quality studies are needed to further examine the effectiveness of strength-based approaches.